Delamination Does Not Affect Outcomes After Arthroscopic Rotator Cuff Repair as Compared With Nondelaminated Rotator Cuff Tears: A Study of 1043 Consecutive Cases. Issue 3 (March 2019) - Kwon, Jieun; Lee, Ye Hyun; Kim, Sae Hoon; Ko, Jung Hoon; Park, Byung Kyu; Oh, Joo Han
Background: Limited information is available regarding the characteristics of delaminated rotator cuff tears as compared with nondelaminated tears. Furthermore, there is conflicting information regarding the effects of delamination on the anatomic healing of repaired cuffs. Purpose: To evaluate the characteristics and anatomic outcomes of delaminated rotator cuff tears in comparison with nondelaminated tears to determine whether delamination is a negative prognostic factor affecting rotator cuff repair outcomes. Study Design: Cohort study; Level of evidence, 3. Methods: Between 2010 and 2014, 1043 patients were enrolled in the study to assess the prevalence of delamination. Among them, the findings from 531 patients who underwent magnetic resonance imaging or computed tomographic arthrography at least 1 year after surgery were included to determine whether delamination was a negative prognostic factor affecting the anatomic outcomes of arthroscopic rotator cuff repair. Delamination was assessed intraoperatively and defined by distinguishable edge cleavage tearing or interstitial horizontal gap between the articular and bursal surfaces of the torn tendon. One of 3 repair techniques (modified Mason Allen, single row, or double row) was used according to tear configuration and tendon mobilization. The authors evaluated visual analog scale scores for pain and satisfaction and American Shoulder and Elbow Surgeons scores to quantify clinical outcomes. Results: The incidence of delamination was 42.9% (447 of 1043). As compared with those with nondelaminated tears, patients with delaminated tears were older ( P < .001) and had longer symptom duration ( P = .019), larger tear sizes and retractions ( P < .001 for both), higher grades of fatty infiltration of the rotator cuff muscles (all P < .001), and poorer tendon quality ( P < .001). The overall healing failure rate was 19.0% (101 of 531). In univariate analysis, the rate of healing failure for the repaired cuffs was significantly higher in the delaminated group (delaminated tears, 60 of 238, 25.2%; nondelaminated tears, 41 of 293, 14.0%; P = .001). However, results of subgroup and multivariate analyses showed that the presence of delamination was ultimately not an independent risk factor for the failure of cuff healing. Between the delaminated and nondelaminated groups, there was no significant difference in postoperative functional outcomes. Conclusion: The results suggest that delaminated rotator cuff tears might represent chronic degenerative tears of longer symptom duration, with larger tear sizes and higher grades of fatty infiltration in older patients. It appears that delamination could be a confounding factor, not an independent prognostic factor, affecting rotator cuff healing.